Migration Policy – An Oxymoron or a Management Project? - Brunsson Karin (Journal of Organizational Sociology)
Arguably, standardization is a key concept in contemporary global society. Not only has standardization facilitated worldwide trade of goods and services, but it has also made people amenable to similar work situations and to the production and consumption of similar products and similar information across countries. Harsh regional and national migration policies negate these effects of globalization and reflect instead a – unrealistic – managerial ideal of order. It is suggested that legislators who seek to transform states into nation states mistake states for organizations. They take an instrumental approach to citizens and migrants and see the declaration of human rights as an insignificant mission statement.